Implementation of Components of The Online Learning Education System In Elementary Schools - Apriyanti Widiansyah; Fara Diba Catur Putri (International Journal of Educational Management and Innovation, 2022)
Implementing online learning amid the Covid-19 Pandemic has caused problems for teachers and students at the elementary school education unit level. This study aims to obtain a comprehensive picture of the implementation of online learning. The approach used is descriptive and qualitative with the case study method. The results of this study are online learning conducted at SDN Harapan Jaya IX by using learning media in the form of videos and social media WhatsApp. The school made efforts to implement online learning during the Covid-19 pandemic by providing teachers with training in using and using electronic media in learning. The availability of facilities and infrastructure to support online learning in schools has been fulfilled for teachers and students. The school has provided facilities in the form of Wifi, and an internet quota for teachers, so teachers do not spend their money buying packages. Furthermore, the evaluation of learning is carried out by giving assignments and evaluating the process of student activity during the online learning process.